ÃNDICES DE CONSUMO E UTILIZAÃ‡ÃƒO DE CULTIVARES DE AMOREIRA POR Bombyx mori L. - Bortoli, Sergio Antonio de; Montagna, Marco AurÃ©lio; Miranda, JosÃ© Ednilson; Murata, Afonso Takao; Takahashi, Roque (REVISTA DE AGRICULTURA, 2015)
ÃNDICES DE CONSUMO E UTILIZAÃ‡ÃƒO DE CULTIVARES DE AMOREIRA POR Bombyx mori L.